Association of single nucleotide polymorphisms in interferon signaling pathway genes and interferon stimulated genes with the response to interferon therapy for chronic hepatitis C - Su, Xiaowen (2008)
BACKGROUND/AIM: Interferon signaling pathway genes (IPGs) and interferon stimulated genes (ISGs) are associated with the host response to hepatitis C virus (HCV) infection. We studied single nucleotide polymorphisms (SNPs) in IPGs and ISGs for their associations with response to pegylated interferon α-2a (Peg-IFN-α) plus ribavirin therapy in HCV genotype-1 infected patients. METHODS: A two-stage study design was used. First, 91 SNPs from 12 IPGs and 9 ISGs were genotyped in a cohort of 374 treatment-naïve HCV patients and assessed for association with sustained viralogic response (SVR). Next, 14 potentially functional SNPs from the OASL gene were studied in this cohort. RESULTS: Three OASL SNPs (rs3213545 and rs1169279 from stage I, and rs2859398 from stage II), were significantly associated with SVR [rs3213545: p=0.03, RR=1.27 (1.03–1.58); rs1169279: p=0.02, RR=1.32 (1.05–1.65); rs2859398: p=0.02, RR=1.29 (1.04–1.61)] after adjusting for other covariates. Further analysis showed these 3 SNPs independently associated with SVR. Additionally, a similar trend towards the associations of these 3 SNPs with SVR was observed in a smaller, independent HCV cohort consisting of subjects from a number of clinical practice settings. CONCLUSIONS: Our study suggests that OASL variants are involved in the host response to IFN-based therapy in HCV patients.